Cereal root exudates contain highly structurally complex polysaccharides with soil‐binding properties. (17th July 2020) - Galloway, Andrew F.; Akhtar, Jumana; Marcus, Susan E.; Fletcher, Nathan; Field, Katie; Knox, Paul
Summary: Rhizosheaths function in plant−soil interactions, and are proposed to form due to a mix of soil particle entanglement in root hairs and the action of adhesive root exudates. The soil‐binding factors released into rhizospheres to form rhizosheaths have not been characterised. Analysis of the high‐molecular‐weight (HMW) root exudates of both wheat and maize plants indicate the presence of complex, highly branched polysaccharide components with a wide range of galactosyl, glucosyl and mannosyl linkages that do not directly reflect cereal root cell wall polysaccharide structures. Periodate oxidation indicates that it is the carbohydrate components of the HMW exudates that have soil‐binding properties. The root exudates contain xyloglucan (LM25), heteroxylan (LM11/LM27) and arabinogalactan‐protein (LM2) epitopes, and sandwich‐ELISA evidence indicates that, in wheat particularly, these can be interlinked in multi‐polysaccharide complexes. Using wheat as a model, exudate‐binding monoclonal antibodies have enabled the tracking of polysaccharide release along root axes of young seedlings, and their presence at root hair surfaces and in rhizosheaths. The observations indicate that specific root exudate polysaccharides, distinct from cell wall polysaccharides, are adhesive factors secreted by root axes, and that they contribute to the formation and stabilisation of cereal rhizosheaths. Significance Statement: Molecular details of the adhesive factors that function in rhizosheath formation and stabilisation are unknown. Here we describe the biochemistry of polysaccharides with soil‐binding properties released by wheat and maize roots, and the use of glycan monoclonal antibodies to track these polysaccharide exudates at the root−soil interface.